The business of portfolio management : boosting organizational value through portfolio management - Fraser, Iain, 1955- (Project Management Institute, Inc., 2017)
"Today there is a gap between organizational strategy and day-to-day management activities. To capitalize on new opportunities, or "getting ahead" rather than just "staying in business," most workplaces need a radical transformation. This transformation can begin with how organizations devise and manage their portfolios. Long underutilized as a mechanism to provide value, portfolio management is now being recognized as an effective approach to bridging these critical business elements. The Business of Portfolio Management offers keys to adopting a new approach to portfolio management that boosts organizational value. A veteran in the field, author Iain Fraser proposes a solution that lies in using the value management framework to link organizational strategy to portfolio content and to delivery mechanisms. In this expansive guide, case study examples illuminate in-depth discussions explaining the value management framework, implementation and delivery techniques, portfolio leadership qualities, key roles and professional development, and change management. Also included is an overview of organizational maturity models to evaluate project, program, and portfolio performance as well as tools and techniques to implement, execute, and measure their benefits and value contribution. To capture success, every organization should ultimately thrive in a culture that embraces its purpose, people, and performance (or the "3Ps to success"), so that aligned activity and empowered people can achieve the confidence to deploy true portfolio management, which is how The Business of Portfolio Management does business that adds value to any organization"--